Preserved european cultural heritage in agrarian landscape of Slovakia - Štefunková, Dagmar; Dobrovodská, Marta (TÁJÖKOLÓGIAI LAPOK, 2009)
The integral part of the cultural heritage in Europe are agricultural historical landscape structures. In Slovakia they represent well preserved historical landscape structures. They are the results of the interaction between natural conditions, geographical position, cultural-historical and economic development. Their recent existence is caused by the marginal position and low natural potential for intensive agriculture. Their origin and being are is necessarily linked to specific human agricultural activity. At present, their preservation is very complicated and it requires a multi-functional approach to landscape utilization. In our paper we have aimed at analysis of the agricultural landscape development in Slovakia in general as the territory crossing western and eastern European culture and at characterization of natural and cultural settings of preserved agricultural HLS as well as the possibilities of their preservation and maintenance in the selected 3 model areas – Svätý Jur, a town near the Bratislava capital city, Liptovská Teplička, a village in the Low Tatras Mts. and Osturňa, a village in the Spišská Magura Mts., with regard to sustainable development and multi-functional landscape utilization.